Development of a M cell‐targeted microparticulate platform, BSK02™, for oral immunization against the ovarian cancer antigen, sperm protein 17. Issue 1 (4th March 2018) - Mattila, Juha‐Pekka; Mirandola, Leonardo; Chiriva‐Internati, Maurizio
Abstract: Although it only accounts for approximately 5% of all female cancer cases, ovarian cancer (OC) ranks as the fifth leading cause of death due to cancer in women. We have evaluated the potential of an orally administered microparticulate vaccine incorporating an immunodominant epitope peptide derived from the cancer/testis antigen sperm protein 17 (SP17) aberrantly expressed in OC, to retard the progression of the disease. The peptide antigen and the immune‐stimulatory toll‐like receptor 9 ligand CpG oligonucleotide were incorporated into spray dried microparticles composed of enteric and sustained release polymers together with the Aleuria aurantia lectin targeting microfold cells present in the gut‐associated lymphoid tissue. These particles were administered via oral route to mice challenged week prior with SP17‐expressing ID8 OC cells. Analysis of splenocytes harvested from vaccinated mice revealed strong activation of IFN‐γ+/CD8+ lymphocytes in response to re‐stimulation with the SP17 antigen. Moreover, vaccinated animals showed significant retardation of ascites/tumor volume in comparison to placebo‐treated animals four weeks after the tumor challenge ( p = 0.005). Taken together, our results suggest that vaccination against SP17 using orally administered microparticles could potentially be used as an effective consolidation strategy for OC patients with residual tumor or high probability for relapse following first‐line treatments. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 29–36, 2019.